PERBEDAAN KEMAMPUAN BERPIKIR KRITIS LAKI-LAKI DAN PEREMPUAN PADA MATERI SISTEM PEREDARAN DARAH MATA PELAJARAN BIOLOGI KELAS XI MIPA MAN I BANYUASIN III - Erna Dwi Yanti; Indah Wigati; Ummi Hiras Habisukan (Bioilmi: Jurnal Pendidikan, 2019)
The ability of critical thinking is very important to have. If the students have an ability of critical thinking, they students can solve the problems that facing them on the lesson study especially biology. Based on that problem, the writer was conducted a research which have the aim to know the difference between the ability of male students’ and female students’ critical thinking on blood circulation system material in biology lesson of XI MIPA MAN 1 Banyuasin. This research was conducted on july 17, 2018 At XI MIPA class of MAN 1 Banyuasin. This research was descriptive analysis research. The subject of this research was the students of XI MIPA 1, XI MIPA 2, XI MIPA 3 XI MIPA 4 of MAN 1 Banyuasin with the total of the students are 157 students. Data analyzing technique used probability sampling technique that is proportionate stratified random sampling with descriptive analysis method, the result of this research showed that the ability of male students’ critical thinking are low with the average 13.15. The ability of female students’ critical thinking are high with the average 14.05. There is the difference between the ability of male studets’ and female students’ critical thinking. In conclusion, the ability of female students’ critical thinking is higher than male student’s in MAN 1 Banyuasin.